Neurochirurgische Operationsmöglichkeiten bei posteriorer Epilepsie - Rössler, Karl; Kasper, Burkhard; Tomschik, Matthias; Dörfler, Arnd; Buchfelder, Michael; Dorfer, Christian (Zeitschrift für Epileptologie, 2021)
Background: The surgical treatment of posterior epilepsy within the spectrum of epilepsy surgery represents a particular challenge. Objective: To present the different surgical options for epilepsy surgery of posterior epilepsies. Material and methods: The different surgical procedures are illustrated in the light of the historical development and recent technical developments. Results: Invasive monitoring (implantation of electrodes), resective and disconnective procedures in combination with new technical developments led to an improvement in seizure outcome in the surgical treatment of posterior epilepsies.
CRIS-Team Scopus Importer:2021-01-15
Keywords: ECoG; Epilepsy surgery; Lesionectomy; Posterior disconnection; Tailored lesionectomy